(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
A cyclone separator holds signiﬁcant importance as the primary gas–solid separation apparatus in the industrial sector. Cyclone separators operate based on a fundamental principle, primarily harnessing the centrifugal force produced by the rotation of air in order to segregate solid particles from the gas stream and then collect them. In addition to the main vortex in the ﬂow ﬁeld, there are a number of secondary ﬂows, which signiﬁcantly impact the aggregation of ﬁne particles and contribute to the heightened energy consumption.